Quantitative interpretation of mineralogical composition from X-ray and chemical data for the Pierre Shale - Schultz, Leonard Gene, 1926- (Professional paper (Geological Survey (U.S.)), 1964)
"Derivation, reproducibility, and accuracy of modal analyses and calculation of composition of montmorillonitic components."